Inside the transnational social space: Cross-border management and owner relationship in a German subsidiary in Hungary - Chistoph Dörrenbächer (Journal for East European Management Studies, 2007)
This paper examines the social relationships in and around a German subsidiary in Hungary during the first 15 years of Hungarian transition to a market economy. It draws on a recent conceptual framework that sees multinational corporations as transnational social spaces, in which transnational communities - communities of individuals that exhibit a unique cross-national organisational identity - may emerge. Empirically investigating two basic types of cross-border social relationship in multinational corporations, the paper argues that, due to the constant interplay of crossborder management and ownership relationships, the emergence of transnational communities is a demanding process, with established communities being precarious entities. – – Aufbauend auf ein aktuelles Konzept, das multinationale Unternehmen als transnationale soziale Räume begreift, beschäftigt sich dieser Beitrag mit den grenzüberschreitenden Sozialbeziehungen einer deutschen Tochtergesellschaft in Ungarn. Im Detail untersucht der Beitrag wie sich die Management- und Eigentümerbeziehungen in der genannten Tochtergesellschaft über die ersten 15 Jahre des Transformationsprozesses hinweg entwickelt haben. Hauptargument ist dabei, dass grenzüberschreitende Sozialbeziehungen in multinationalen Unternehmen aufgrund des Wechselspiels von Management- und Eigentümerbeziehungen nur selten die Form transnationaler Gemeinschaften (Gemeinschaften, die eine besondere grenzüberschreitende organisationale Identität ausbilden) annehmen.
Keywords: 650; Multinational corporations; Transnational social space; Transnational communities; Headquarters-subsidiary relationships; Knowledge transfer